2019
DOI: 10.1108/sjme-10-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive absorption on marketing learning performance

Abstract: Purpose The purpose of this paper is to analyse the individual’s experience during the use of Pinterest in a marketing learning process. This experience is a fundamental starting point from which to develop marketing learning processes that flow naturally. Thus, it is necessary to examine the components that determine the individual’s experience and to explore consequences such as collaborative learning and marketing learning performance. Design/methodology/approach To conceptualise the individual’s experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 103 publications
(125 reference statements)
2
4
0
Order By: Relevance
“…As such, participants’ learning outcomes were examined in Study 2. The results indicated that CA led to different learning outcomes for EFL learners, which echoed previous research that reported better learning outcomes resulting from VR technology [ 59 , 60 ]. Specifically, participants showcased better learning outcomes with VR-based language learning, and this finding is in line with recent research of [ 61 ] and that of [ 62 ].…”
Section: Discussionsupporting
confidence: 77%
“…As such, participants’ learning outcomes were examined in Study 2. The results indicated that CA led to different learning outcomes for EFL learners, which echoed previous research that reported better learning outcomes resulting from VR technology [ 59 , 60 ]. Specifically, participants showcased better learning outcomes with VR-based language learning, and this finding is in line with recent research of [ 61 ] and that of [ 62 ].…”
Section: Discussionsupporting
confidence: 77%
“…In the e-learning and social network context, Cheng (2022) found that CA positively influences cloud-based e-learning continuance intention and performance outcomes. Guinaliu-Blasco et al (2019) also confirmed that CA has a positive effect on collaborative learning and marketing learning performance in social networks.…”
Section: Hypotheses and Research Frameworksupporting
confidence: 60%
“…After the rise of multimedia, CA efficacy has been widely applied in technology media acceptance research and has been found to be a key antecedent for acquiring a deeper understanding of the formation of user beliefs and IS/IT usage intention. Examples include e-learning and mobile learning (Reychav and Wu, 2015a, 2015b; Shah and Soror, 2019; Cheng, 2022), mobile instant messaging (Hou and Shang, 2018; Hou et al , 2019) and social networking site (Hsu et al , 2016; Hsu and Lin, 2017; Guinaliu-Blasco et al , 2019). In the e-learning and social network context, Cheng (2022) found that CA positively influences cloud-based e-learning continuance intention and performance outcomes.…”
Section: Hypotheses and Research Frameworkmentioning
confidence: 99%
“…Islam et al [11] argue that well-designed interfaces re ect a positive experience, ultimately evoking a sense of exploration and motivating the users to use the technologies. It drives the users to enter a state of absorption by satisfying their informational needs [12]. Agarwal and Karahanna [13] conceptualized technological experiences as cognitive absorption.…”
Section: Introductionmentioning
confidence: 99%